PENGEMBANGAN INDIKATOR 4C’s YANG SELARAS DENGAN KURIKULUM 2013 PADA MATA PELAJARAN MATEMATIKA SMA/MA KELAS XI SEMSTER 2 - Wijaya, Achmad Alfian Budi; Sunardi, Sunardi; Kurniati, Dian (Department of Mathematics Education , University of Jember, 2017)
Abstract. This research aims to produce valid 4C’s indicator which is in line with the curriculum of 2013 in mathematics subject of second semester elevent grade of senior high school (SMA/MA). The type of research used is a modified Plomp development model consisting of 4 phases: preliminary investigation, design phase, realization/contruction phase, and test, evaluation and revision phase. The development of this research is the 4C’s indicator which is in line with the curriculum of 2013 in mathematics subjects second semester elevent grade of senior high school (SMA/MA) consisting of 4 chapters, namely: sequence and series, algebraic function limit, algebraic function derivative, and indefinite integral algebra function. The instrument which was used is the validation of 4C’s indicator which is in line with the curriculum of 2013. The results of this development are validated by 5 validators, namely 2 lecturers of Mathematics Education Study Program of Jember University and 3 mathematics teachers of SMAN Arjasa. The results of the development of 4C’s indicator has a coefficient of 3.93 validity results which is categorized as “well”. So the development of 4C’s indiator in line with the curriculum of 2013 in the mathematics subject of second semester elevent grade of senior high school (SMA/MA) has met the criteria of validity. Keywords: Plomp development, 4C’s indicator, 2013 curriculum